2018
DOI: 10.3389/fphar.2018.01082
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Gut Microbiota in Atherosclerosis and Hypertension

Abstract: In recent years, accumulating evidence has indicated the importance of gut microbiota in maintaining human health. Gut dysbiosis is associated with the pathogenesis of a number of metabolic diseases including obesity, type 2 diabetes mellitus (T2DM), non-alcoholic fatty liver disease (NAFLD), and cardiovascular diseases (CVDs). Indeed, CVD has become the leading cause of death worldwide, especially in developed countries. In this review, we mainly discuss the gut microbiota-involved mechanisms of CVD focusing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
145
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 185 publications
(150 citation statements)
references
References 178 publications
(194 reference statements)
4
145
0
1
Order By: Relevance
“…These findings partially support the view that BBR may at least partly improve systemic inflammation and lipid level by regulating gut bacteria related to inflammation and glucolipid metabolism, thereby reducing HFD-induced atherosclerosis. Indeed, evidence is accumulating that gut microbiota and its metabolites, such as SCFAs, TMAO, and secondary bile acids, play a role in atherosclerosis by regulating inflammation and the metabolism of lipid, cholesterol and glucose (Barrington and Lusis, 2017;Jonsson and Backhed, 2017;Kasahara et al, 2017;Ma and Li, 2018). SCFAs have anti-atherogenic effect, in addition, it can inhibit the fat synthesis in enterocytes and adipocytes, and suppress biosynthesis of cholesterol and LDL formation in the liver, besides their anti-inflammatory effects (Chistiakov et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings partially support the view that BBR may at least partly improve systemic inflammation and lipid level by regulating gut bacteria related to inflammation and glucolipid metabolism, thereby reducing HFD-induced atherosclerosis. Indeed, evidence is accumulating that gut microbiota and its metabolites, such as SCFAs, TMAO, and secondary bile acids, play a role in atherosclerosis by regulating inflammation and the metabolism of lipid, cholesterol and glucose (Barrington and Lusis, 2017;Jonsson and Backhed, 2017;Kasahara et al, 2017;Ma and Li, 2018). SCFAs have anti-atherogenic effect, in addition, it can inhibit the fat synthesis in enterocytes and adipocytes, and suppress biosynthesis of cholesterol and LDL formation in the liver, besides their anti-inflammatory effects (Chistiakov et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Studies in the past decade have shown that the gut microbiota is associated with certain human diseases, including obesity (Boulange et al, 2016), type 2 diabetes (Qin et al, 2012), hypercholesterolemia (Martinez et al, 2009) and CVDs (Tang et al, 2017), all of which are associated with atherosclerosis (Jonsson and Backhed, 2017). The role of the gut microbiota in atherosclerosis has begun to be appreciated in recent years, mainly including the regulation of inflammation and immunity, and cholesterol and lipid metabolism by gut microbiota and its metabolites (Jonsson and Backhed, 2017;Ma and Li, 2018). These findings have highlighted the great potential preventative and therapeutic benefits for atherosclerosis that might be realized by targeting the gut microbiome.…”
Section: Introductionmentioning
confidence: 99%
“…Diet plays a significant role in modulating microbial diversity and reports have indicated that a high-fat diet is associated with obesity, whereas a fiber-rich diet has the potential for reducing the risk of obesity [81,82]. Gut microbiota play a critical role in hemostasis for maintaining human health, with gut dysbiosis contributing to the development and progression of various diseases including CVD, obesity, T2DM, NAFLD, and even some types of cancer [83].…”
Section: Impact Of Human Gut Microbiota On Vascular Endothelimmentioning
confidence: 99%
“…This could be attributed to the taming effect of breastfeeding on the adrenocortical function, breastmilk content of endorphin and low salt content in breastmilk (17,18) . Also, there is emerging evidence of the role of microbiota in pathogenesis of hypertensive disease and atherosclerosis and that gut dysbiosis may predispose to CVD (19) . Exclusive breastfeeding has been shown to influence gut microbiota and reduce dysbiosis and thereby contribute to preventing CVD (20) .…”
Section: Discussionmentioning
confidence: 99%